Analisis Keputusan Generasi Z Dalam Penggunaan Pembayaran E-Wallet Ditinjau Dari Perspektif Akuntansi Keperilakuan - Aryani, Intan Syahaliza (Fakultas Ekonomi dan Bisnis Unram, 2025)
This study aims to analyze the financial behavior of Generation Z in using e-wallets from a Behavioral Accounting perspective. The approach used is descriptive qualitative to describe in depth the factors of user behavior. The respondents of this study were 60 active Generation Z students of Mataram University, obtained through a non-probability sampling technique with an incidental sampling approach. Data were collected through an online questionnaire containing indicators of ease of use (perceived ease of use), social influence, money salience, and impulsive behavior, then analyzed descriptively. The results show that perceived ease of use and peer influence are the dominant factors in shaping e-wallet usage intentions. However, intensive promotions such as cashback and discounts also trigger consumptive and impulsive behavior due to low money salience towards digital money. These findings confirm that Generation Z's financial decisions are influenced not only by rational considerations, but also by social and emotional factors. The results of this study are expected to encourage increased digital financial literacy so that e-wallet use is wiser and more balanced.